PERSEPSI PENERIMA LAYANAN TERHADAP KUALITAS PELAYANAN KESEHATAN IBU DAN ANAK: STUDI KUALITATIF DESKRIPTIF DI PUSKESMAS TARIK, KABUPATEN SIDOARJO - Belia Rizki Safitri (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
Maternal and Child Health (MCH) service quality is an important component of primary health care because it relates to maternal and child safety, service accessibility, and user satisfaction. This study aims to describe service recipients’ perceptions of MCH service quality at Tarik Community Health Center, Sidoarjo Regency. A descriptive qualitative approach was used through in-depth interviews with ten informants consisting of pregnant women and mothers of children under five, supported by one MCH coordinating midwife as a triangulation informant. Data were analyzed thematically using five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings show that health workers were generally perceived as competent and polite. However, limited waiting room capacity, long waiting times, inadequate examination room privacy, and inconsistent responsiveness during peak hours remained key concerns. Improvements in facilities, staff distribution, patient information services, and privacy protection are recommended.